INCA : summary and conclusions - C. Neal; P. G. Whitehead; N. Flynn (Copernicus Publications, 2002)
This contribution brings to a close a special issue of Hydrology and Earth System Sciences concerning the assessment of nitrogen dynamics in catchments across Europe within a semi-distributed Integrated Nitrogen model for multiple source assessment in Catchments (INCA). The wide range of issues involved in relation to hydrology and within-catchment processes, scale (from small catchments to major river basins), climate (from sub-arctic to Mediterranean regimes) and pollution (atmospheric, agricultural and urban sources) is outlined. Consideration is then given to how well the model has performed and future research requirements are outlined. Keywords: nitrogen, nitrate, ammonium, organic nitrogen, catchments, streams, rivers, river basins